Multicultural Islamic Education: An Endeavor to Integrate Human Rights Values - Yulianto, Eko; Mokhtar, Ahmad Baha' bin (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
In an era marked by increasing cultural diversity and global interconnectedness, this article critically examines the pivotal role of multicultural Islamic education in instilling Human Rights values within multicultural societies. By fostering an educational paradigm that transcends traditional boundaries, multicultural Islamic education emphasizes the profound internalization of core principles such as tolerance, justice, inclusivity, and non-discrimination. This approach is strategically designed to cultivate moderate (wasatiyah) and humanistic learners who embody Islam's balanced, compassionate ethos across diverse contexts. Drawing on robust theoretical analysis, the study establishes meaningful linkages between universal human rights principles—derived from international frameworks such as the Universal Declaration of Human Rights—and authentic Islamic perspectives. Key Islamic concepts, including human dignity (karāmah al-insān), equality before God, restorative justice ('adl), and religious freedom (hifz al-din), are meticulously aligned with the comprehensive Maqāṣid al-Sharī‘ah framework, which prioritizes the preservation of faith, life, intellect, progeny, and wealth. This integration not only resolves potential tensions between secular and religious worldviews but also enriches both by highlighting Islam's inherent commitment to human flourishing. The article further highlights practical strategies for embedding Human Rights values by promoting tolerance and interfaith dialogue, respect for minority rights, equitable social justice initiatives, and the unequivocal rejection of violence and extremism in Islamic educational curricula. Special emphasis is placed on the indispensable role of teachers and educational institutions as architects of change. Educators, equipped with pedagogical innovations and cultural competence, are positioned as key agents in crafting inclusive, participatory learning environments that encourage critical thinking, empathy, and civic engagement among students from varied backgrounds.